Political views on a further deregulation of the European road haulage market - Stephan Keuchel; Thomas Beckschwarte; Fabian Ernst (Journal of Shipping and Trade (JST), 2020)
Within the broad ongoing review of the legislation of the European road haulage market the European Commission presented in May 2017 several proposals to clarify the regulation of the market, especially market access, driving and rest periods, and the application of the posted workers directive. The paper aims to show economic implications of the suggested regulation on the basis of two round trip models and to outline the differences of political and regional interests by analysing the ammendments to the proposals handed in by members of the political groups of the different Member States. The proposed regulation can be viewed as a further deregulation of the market with further shifts of markets shares in international and cabotage markets. This in turn is reflected by distinct regional differences of amendments of members within the different political groups.
Keywords: 650; European transport policy; Road haulage market; Deregulation; Cabotage; Posting of workers; Interest groups; Policy process